FINANCIAL AND MARKETING PERFORMANCE OF SMALL AND MEDIUM ENTERPRISES IN INDONESIA: A SYSTEMATIC LITERATURE REVIEW - Indra Rachmawati; Gita Rahmadani (ICON Publisher, 2026)
This study systematically reviews the relationship between financial performance and marketing performance in Small and Medium Enterprises (SMEs) in Indonesia with the aim of identifying empirical evidence patterns, metrics used, mechanisms of influence, and research gaps that need to be addressed. Using a systematic literature review approach structured according to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, this study examines empirical studies that discuss financial and marketing indicators. The synthesis results show that financial and marketing performance are multidimensionally interrelated. Marketing capabilities including marketing implementation, marketing communication, channel management, and product innovation consistently contribute to improved marketing performance and customer performance, while the direct effect on financial performance is often mediated by managerial capabilities and external support such as financial assistance programs. The findings also confirm the role of digital transformation as an enabler that strengthens both areas of performance through operational efficiency, broader market access, and real-time analytical capabilities. Based on these findings, further research is recommended to apply a longitudinal design and test the mediating and moderating roles of managerial capabilities using techniques such as Structural Equation Modeling (SEM). The practical implications emphasize the need for integrated performance measurement, improved financial literacy and managerial capabilities, and a priority on measurable digitization to support the sustainability and competitiveness of SMEs in Indonesia